2016
DOI: 10.1038/ncomms12021
|View full text |Cite
|
Sign up to set email alerts
|

Treg engage lymphotoxin beta receptor for afferent lymphatic transendothelial migration

Abstract: Regulatory T cells (Tregs) are essential to suppress unwanted immunity or inflammation. After islet allo-transplant Tregs must migrate from blood to allograft, then via afferent lymphatics to draining LN to protect allografts. Here we show that Tregs but not non-Treg T cells use lymphotoxin (LT) during migration from allograft to draining LN, and that LT deficiency or blockade prevents normal migration and allograft protection. Treg LTαβ rapidly modulates cytoskeletal and membrane structure of lymphatic endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(97 citation statements)
references
References 52 publications
(75 reference statements)
6
90
0
Order By: Relevance
“…A recent study suggested a role for LEC-expressed VCAM-1 in homeostatic migration of nT reg but not of naïve CD4 + or CD8 + T cells from skin to the dLN (67). VCAM-1 is a known target of LTβR (136) and blockade of LTβR reduced nT reg exit from the skin (67).…”
Section: T Cell Entry and Migration Within Afferent Lvsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study suggested a role for LEC-expressed VCAM-1 in homeostatic migration of nT reg but not of naïve CD4 + or CD8 + T cells from skin to the dLN (67). VCAM-1 is a known target of LTβR (136) and blockade of LTβR reduced nT reg exit from the skin (67).…”
Section: T Cell Entry and Migration Within Afferent Lvsmentioning
confidence: 99%
“…VCAM-1 is a known target of LTβR (136) and blockade of LTβR reduced nT reg exit from the skin (67). Similarly, fewer nT reg devoid of the LTβR ligand, LTα, exited from the skin (67).…”
Section: T Cell Entry and Migration Within Afferent Lvsmentioning
confidence: 99%
See 1 more Smart Citation
“…While a literature search to biologically explain each gene of the 32-gene signature was not part of the current study, one gene of that particularly struck interest was Lymphotoxin Beta (LTB), which was elevated in cluster1 patient tumor samples. Interestingly, LTB has been shown to specifically stimulate Tregs to migrate from the tissue to the lymph nodes via afferent lymphatics [37]. This therefore may at least partly attribute the positive clinical associations of cluster1 patients to elevated LTB expression, which may be directing immunosuppressive Tregs away from tumor tissue sites, thus unleashing the antitumor response within cluster1 tumor samples.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, T Reg cells as well as central memory T cells, but not effector memory or effector T cells, also maintain high levels of CCR7 expression and reside in the LN. When comparing cell populations in afferent vs. efferent lymph, the efferent was found to be mostly composed of T cells, with more CD4 + vs. CD8 + T cells [47,48], while afferent lymph consisted mostly of αβ T cells, efficient than CD8 + T cells at exiting peripheral tissue via afferent lymphatics [49][50][51][52], and of the T cells found in the afferent lymph, most are either memory or T Reg cells [50,[53][54][55][56]. However, some research has suggested that naïve T cells may use afferent lymphatics when migrating from peripheral tissues [51,[57][58][59][60].…”
Section: Lymphatic Transport Of Leukocytesmentioning
confidence: 99%